1996
DOI: 10.1007/s001250050577
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of a missense mutation of the glucokinase gene in gestational diabetic patients due to a founder-effect in a local population

Abstract: A high proportion of the female patients who are members of maturity onset diabetes of the young (MODY) pedigrees, and whose diabetes mellitus is due to a glucokinase mutation, originally presented with gestational diabetes. To establish whether glucokinase mutations could be a common cause of gestational diabetes, we studied 50 subjects who presented with gestational diabetes and on follow-up had hyperglycaemia (5.5-10.0 mmol/l). Screening for glucokinase mutations using single-stranded conformational polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 20 publications
3
51
1
Order By: Relevance
“…All known forms of MODY are primarily linked with pancreatic ␤-cell dysfunction. Previous studies have shown that mutations in the GCK (MODY2) gene could explain ϳ5-6% of GD in different populations (12)(13)(14). In our previous study of early onset diabetes, 11 of 29 diabetic women with MODY3 (38%) had had GDM (15).…”
mentioning
confidence: 85%
“…All known forms of MODY are primarily linked with pancreatic ␤-cell dysfunction. Previous studies have shown that mutations in the GCK (MODY2) gene could explain ϳ5-6% of GD in different populations (12)(13)(14). In our previous study of early onset diabetes, 11 of 29 diabetic women with MODY3 (38%) had had GDM (15).…”
mentioning
confidence: 85%
“…Approximately 2% (range 0-6%) of women with a diagnosis of gestational diabetes mellitus have a heterozygous GCK gene mutation (23,34,(46)(47)(48)(49)(50)(51)(52)(53) (16,19,55). The raised fasting glucose is not correlated with BMI (54) so occurs to a similar degree in both slim and obese individuals.…”
Section: Prevalence Of Gck-mody In Gestational Diabetes Mellitusmentioning
confidence: 99%
“…Women with mutations in GCK [12][13][14][15][16][17] or HNF1A [16,18] often present with GDM. In addition, mutations in IPF1 have been reported in women with GDM [16,19].…”
Section: Introductionmentioning
confidence: 99%